Control of α -particle confinement in the helical device for fusion with “magnetic axis sweeping” - Shishkin, A.; Motojima, O.; Moskvitina, Yu.; Eremin, O.; Jun-ichi Miyazawa; Masuzaki, S.; Yamada, H.; Mitarai, O.; Morisaki, T.; Ohyabu, N. (Вопросы атомной науки и техники, 2008)
We examine here the possibility to control the a-particle confinement where a-particles appear as the products of the D+³₂He fusion in the experiment on Large Helical Device /LHD/. We study here the specific for the torsatron / heliotron device method, namely the control of the torsatron / heliotron magnetic configuration and confinement properties with the use of the poloidal field (PF) coils. The proposed here method can be used in DEMO–grade helical reactor Force Free Helical Reactor /FFHR/.